Method Of Teaching Speaking To The Seventh Grade Students Of SMP Muhammadiyah 2 Surakarta In 2014/ 2015 Academic Year - Indriyani, Indriyani; , Aryati Prasetyarini, S.Pd, M.Pd; , Drs. Djoko Srijono, M.Hum (2015)
This research aims at describing the method of teaching speaking to the seventh grade students of SMP Muhammadiyah 2 Surakarta in 2014/2015 academic year. This research is a descriptive research. The subject of this research is the English teacher and students of SMP Muhammadiyah 2 Surakarta. The object of the research is the implementation method to teaching speaking to the seventh grade students of SMP Muhammadiyah 2 Surakarta. The data are taken from event, informant, and document. The methods of collecting data in this research are observation, interview, and document analysis. The research finding shows that the writer did interview the English teacher and the students. Based on the data analysis, the teacher used Communicative Teaching Learning (CLT) and Inquiry Based Learning (IBL). The goal of teaching speaking is to develop the students' courage to speak English. The writer finds the problem faced by the teacher, namely the student different competence and classroom management. The English teacher solved the problems by using some techniques such as the teacher role playing, games, problem solving, discussion, and song. The teacher also always gave motivation to the students about the importance of their activity in speaking class. In teaching learning process if the students did not understand, the materials was repeated by the teacher slowly and clearly